2008
DOI: 10.3141/2083-16
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Urban Arterial Crashes Relative to Proximity to Intersections and Injury Severity

Abstract: Intersections of an urban arterial corridor may influence crashes that occur even beyond their physical area. This study examines the effect of the gradual change in the distance of intersection influence on crash characteristics that explain injury severity outcomes of arterial crashes. The approach adopted involves simultaneous estimation of two variables: an ordinal variable representing crash-injury severity and a binary variable representing crash location (intersection versus segment crashes). The dichot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…Hence the increase in speeds and less attention by the drivers could lead to crashes with severe injuries. Das et al (2008) had found similar results. On the same corridor group, older drivers (N55 yrs) also are involved in severe rear-end crashes.…”
Section: Rear-end Crashessupporting
confidence: 88%
See 2 more Smart Citations
“…Hence the increase in speeds and less attention by the drivers could lead to crashes with severe injuries. Das et al (2008) had found similar results. On the same corridor group, older drivers (N55 yrs) also are involved in severe rear-end crashes.…”
Section: Rear-end Crashessupporting
confidence: 88%
“…For example, in Florida, all the crashes occurring within 250 ft. from the center of an intersection are categorized as intersection related crashes, as has been reported by Abdel-Aty and and Wang, Abdel-Aty, and Brady (2006). Recently Das, Pande, Abdel-Aty, and Santos (2008) showed that proximity only is not the best way to assign crashes. Wang, Abdel-Aty, Nevarez, and Santos (2008) used frequency modeling for crashes with fixed as well as varying influence distance and found a different set of significant factors.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, the Texas Department of Transportation (2015) defines an intersection crash as the crash in which the first harmful event occurs within the limits of an intersection, and an intersection-related crash is a crash in which the first harmful event occurs on an approach to or exit from an intersection and results from an activity, behavior, or control related to the movement of traffic units through the intersection. In Florida, the physical area of an intersection is considered to be the area within 50 ft of the center of the intersection (Das et al 2008). In Australia, the Transport for New South Wales (2015) defines an intersection crash as "a crash where the first impact occurs at or within 10 m of an intersection."…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous intersection crash analysis articles are available, few studies focus on the crash characteristics of intersection approach crashes and their influencing factors. Das et al (2008) studied the effect of distance from the center of the intersection on characteristics of urban arterial crashes. They suggested that severity of arterial crashes (intersection crashes and midblock segment crashes) might be modeled independently of crash location if the intersection crash occurred within 100 ft of the center of intersection.…”
Section: Introductionmentioning
confidence: 99%